The Administrative Capability of the Barangay Governments in the Municipality of Jolo, Philippines - Basaluddin, Kadafi A. (Open Access Indonesia Journal of Social Sciences, 2021)
This research aims to assess the administrative capability of the barangay governments in the Municipality of Jolo, find out factors adversely affecting the capability of these barangays, and propose an alternative capability-building approach suitable for the subject barangays. This study utilized a descriptive method which involved one hundred nineteen (119) study samples determined through Purposive sampling. The administrative strength of the barangay governments in Jolo is mainly confined to the construction of rock-caused-ways and footbridges. Other pressing problems in the community remained poorly addressed to the dismay of their respective constituents. Their capability of discharging the devolved function as required in the LGC of 1991 is minimal. By and large, the barangay governments in Jolo failed to fully realize the expectations of the code and to address the daily concerns of their constituents with utmost efficiency and effectiveness. Their capability is adversely affected by factors such as scarcity of resources, inadequate training, insufficient political support, poor inter-governmental coordination, and lack of accountability. The administration of most of these units is characterized by gross inefficiency, nepotism, and a patronage system. The proposed alternative approach to enhancing the administrative capability of these units focused on the internal value reformation which is mainly anchored on the Islamic system of leadership which are suitable due to the fact that all barangay officials in Jolo are Muslims. Besides, any approach toward improving administrative capability will be doomed to fail if the local officials do not have the proper moral values. Local units possess a different levels of administrative capability. Hence, decentralization has to match with local capability and endowments. Thus, there is a need to revisit the code should the benefits of local autonomy is to be fully reaped.